Dispute Resolution of Certified Land Rights in Sale and Purchase Transactions: Case Study of Lawsuit for Unlawful Acts - Tarigan, Alberto Paskah; Debora, D. (Manunggal Halim Jaya, 2025)
The resolution of disputes over certified land rights in purchase and sale transactions is a crucial issue in agrarian law in Indonesia. Legal uncertainty often arises due to double claims, incomplete documents, or disputes between parties claiming to have the same land rights. The existence of a land right certificate is the result of the land registration process. As stated in Article 19 paragraph (2) of the UUPA, land registration includes several series of activities that end with the provision of valid proof of rights as a valid means of proof. This study aims to analyze the dispute resolution mechanism and the role of legal institutions and land administration in ensuring legal certainty. Thus, it can be said that a right to the land has a certificate as proof of its rights. On the other hand, if a land right does not have a certificate, it means that the land is registered as required by the applicable laws and regulations, the method used is a qualitative approach with case studies in several areas that experience land rights disputes. The results of the study show that mediation and arbitration can be an effective alternative settlement before taking the litigation route. In addition, the importance of transparency in the land certification process and legal education for the community is the main highlight to reduce conflicts. These findings are expected to provide recommendations for policymakers and the public in maintaining the stability of land rights in Indonesia.